Public sector net worth as a fiscal target - Ben Zaranko (Institute for Fiscal Studies (IFS), 2023)
We consider the case for and against a fiscal target for public sector net worth.
Keywords: 330; Government finances and spending; IFS Green Budget 2023; Fiscal rules and frameworks; Investment; Public finance; Public sector